121k views
3 votes
How do you solve this? cosθ-tanθcosθ=0

1 Answer

1 vote
First, lets note that
tan(\theta)\cdot cos(\theta)=sin(\theta). This leads us with the following problem:


cos(\theta)-sin(\theta)=0

Lets add sin on both sides, and we get:


cos(\theta)=sin(\theta)

Now if we divide with sin on both sides we get:


(cos(\theta))/(sin(\theta))=1

Now we can remember how cot is defined, it is (cos/sin). So we have:


cot(\theta)=1

Now take the inverse of cot and we get:

\theta=cot^(-1)(1)=\pi\cdot n+ (\pi)/(4) , \quad n\in \mathbb{Z}

In general we have
cot^(-1)(1)=(\pi)/(4), the reason we have to add pi times n, is because it is a function that has multiple answers, see the picture:

How do you solve this? cosθ-tanθcosθ=0-example-1
User Laxmidi
by
5.7k points